Vibrotactile fingertip stimulation: fmri investigation of brain activation, ica connectivity, and percent signal change - Seri, Faten Anis Syairah (2025)
Vibrotactile stimulation is a valuable tool for investigating somatosensory processing, but the effects of varying stimulation frequencies on neural activity and network connectivity are not fully understood. This study investigated the impact of different vibrotactile frequencies on brain activation and functional connectivity within the somatosensory cortex. Twenty healthy, right-handed participants (14 males, 6 females; mean age 25.1 ± 5.01 years) were scanned using 3.0 T MRI during vibrotactile stimulation (30-480 Hz) with piezoelectric vibrator attached at index fingertips. Frequency-specific comparisons revealed greater activation in the right putamen at 90 Hz compared to 120 Hz, potentially related to habituation during motor control learning. Conversely, 120 Hz stimulation, relative to 150 Hz, resulted in significant activation in the left precentral gyrus, right lingual gyrus, right thalamus, right cerebellar lobules 4_5, and right Rolandic operculum, suggesting greater efficacy of lower frequencies. Regarding functional network connectivity, high connectivity between the auditory network (AUN) and visual network (VIN) suggests synchronized activity. Strong functional connectivity between the default mode network (DMN) and VIN suggests sub-networks or clusters within the larger functional network. These interconnected regions (AUN, DMN, VIN), particularly VIN, may form a functional module, with VIN playing a central role in information integration. Moderate positive connectivity between AUN and the sub-cortical domain network (SCN) indicates some synchronized activity. Weak connectivity between the sensorimotor network (SMN) and cognitive control network (CCN) implies minimal functional relationship. Negative connectivity between SCN and SMN suggests anticorrelated activity patterns, possibly reflecting distinct sub-networks. A region of interest (ROI) analysis compared percent signal change between low and high-frequency conditions within the medial frontal gyrus (MFG), paracentral lobule (PaCL), precentral gyrus (PreCG), postcentral gyrus (PoCG), inferior parietal lobule (IPL), and cingulate gyrus (CgG). The Wilcoxon Signed-Rank test revealed significant differences in BOLD signal change between low and high-frequency stimulation in the PaCL (Z = -2.14, p = 0.03, rrb = -0.338), PreCG (Z = -2.46, p = 0.01, rrb = -0.389), PoCG (Z = -2.41, p = 0.01, rrb = -0.381), and CgG (Z = -3.58, p = 0.001, rrb = -0.566), indicating differential processing of high-frequency input. The MFG (Z = -0.97, p = 0.33, rrb = -0.153) and IPL (Z = -1.76, p = 0.08, rrb = -0.278) showed no significant differences, suggesting less direct modulation by vibrotactile frequency. This study provides evidence for distinct neural responses to low and high-frequency vibrotactile stimulation. Observed functional connectivity patterns suggest network cooperation during vibrotactile processing. Our findings demonstrate that activation within S1 and S2 is modulated by vibrotactile frequency, contributing to a deeper understanding of somatosensory processing. Future studies could investigate hub roles, explore different frequency ranges and intensities, and examine clinical implications for sensory processing deficits.